The icon project architecture, cities, and capitalist globalization - Sklair, Leslie 1940- (Oxford University Press, 2017)
"A pioneering look at the ways in which contemporary architecture serves the interests of the capitalist class, from global North to South and through to the petro-cities of the Gulf States In the last quarter century, a new form of iconic architecture has appeared throughout the world's major cities. Typically designed by globe-trotting "starchitects" or by a few large transnational architectural firms, these projects are almost always driven by private interests. In The Icon Project, sociologist Leslie Sklair focuses on ways in which capitalist globalization is produced and represented all over the world, especially in globalizing cities. Sklair traces how the iconic buildings of our era-elaborate shopping malls, spectacular museums and vast urban megaprojects-constitute the triumphal "Icon Project" of contemporary global capitalism, promoting increasing inequality and hyperconsumerism. He sets out to explain how the architecture industry organizes the social production and marketing of iconic structures and how corporations increasingly dominate the built environment and promote the trend towards globalizing, consumerist cities. The Icon Project, Sklair argues, is a weapon in the struggle to solidify capitalist hegemony as well as reinforce transnational capitalist control of where we live, what we consume, and how we think" ...